2017
DOI: 10.1016/j.jastp.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

First observations of electron gyro-harmonic effects under X-mode HF pumping the high latitude ionospheric F-region

Abstract: Abstract. We provide the first experimental evidence of the sensitivity of phenomena induced 26 by extraordinary (X-mode) polarized HF high power radio waves to pump frequency stepping 27 across the fifth electron gyro-harmonic (5fce) from below to above. The results were obtained at 28 the EISCAT (European Incoherent Scatter Scientific Association) HF heater facility near Tromsø 29 under effective radiated powers of 456 -715 MW, when the HF pump wave was transmitted into 30 the magnetic zenith. We have analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…As shown by Blagoveshchenskaya et al (2014Blagoveshchenskaya et al ( , 2015, the HFPLs and HFILs were generated through the whole X-mode transmission pulse at various high heater frequencies both below and above the critical frequency of the F 2 layer (f H ≤ f o F 2 and f o F 2 < f H ≤ f o F 2 + f ce /2, where f ce is the electron gyroharmonic frequency). In the course of the X-mode HF pumping experiments, the excitation of Langmuir and ion-acoustic plasma waves was accompanied by the generation of artificial small-scale FAIs (Blagoveshchenskaya et al, 2011(Blagoveshchenskaya et al, , 2013(Blagoveshchenskaya et al, , 2015, very strong radio-induced optical emissions in red and green lines (Blagoveshchenskaya et al, 2014), and the narrowband stimulated electromagnetic emission within 1 kHz of the heater frequency recorded at a distance of 1,200 km from the EISCAT/Heating facility (Blagoveshchenskaya et al, 2015;Blagoveshchenskaya, Borisova, Kalishin, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As shown by Blagoveshchenskaya et al (2014Blagoveshchenskaya et al ( , 2015, the HFPLs and HFILs were generated through the whole X-mode transmission pulse at various high heater frequencies both below and above the critical frequency of the F 2 layer (f H ≤ f o F 2 and f o F 2 < f H ≤ f o F 2 + f ce /2, where f ce is the electron gyroharmonic frequency). In the course of the X-mode HF pumping experiments, the excitation of Langmuir and ion-acoustic plasma waves was accompanied by the generation of artificial small-scale FAIs (Blagoveshchenskaya et al, 2011(Blagoveshchenskaya et al, , 2013(Blagoveshchenskaya et al, , 2015, very strong radio-induced optical emissions in red and green lines (Blagoveshchenskaya et al, 2014), and the narrowband stimulated electromagnetic emission within 1 kHz of the heater frequency recorded at a distance of 1,200 km from the EISCAT/Heating facility (Blagoveshchenskaya et al, 2015;Blagoveshchenskaya, Borisova, Kalishin, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Here we present two X-mode heating experiments operated on 21 and 22 October 2012, which provide evidence to survey the aspect dependence of PI excited by X-mode EM heating wave. These two experiments were performed by the Russian team to study the X-mode HF heater-induced phenomena in the F region of the ionosphere [Blagoveshchenskaya et al, 2015[Blagoveshchenskaya et al, , 2017. The EISCAT UHF radar is able to observe the Langmuir wave and ion acoustic wave (IAW) propagated along the radar beam.…”
Section: Observationsmentioning
confidence: 99%
“…Although X-mode heating effects have been discussed by many researchers, until recently, Blagoveshchenskaya et al [2011Blagoveshchenskaya et al [ , 2013Blagoveshchenskaya et al [ , 2014Blagoveshchenskaya et al [ , 2015Blagoveshchenskaya et al [ , 2017 reported the direct evidence of PI excitation by using the European Incoherent Scatter (EISCAT) observations. During X-mode heating experiments, a great number of nonlinear phenomena are observed, such as small-scale field-aligned irregularities [Blagoveshchenskaya et al, 2011[Blagoveshchenskaya et al, , 2013[Blagoveshchenskaya et al, , 2015, enhanced airglow [Blagoveshchenskaya et al, 2014], narrowband SEEs [Blagoveshchenskaya et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the narrow SEE spectra may be associated with the ion acoustic wave, electrostatic ion cyclotron wave, and electrostatic ion cyclotron harmonic wave. Blagoveshchenskaya et al () demonstrated experimental results on the behavior and intensities of various spectral lines in the narrowband SEE spectra within 1 kHz of the heater frequency, depending on the pump frequency stepping across the fifth electron gyroharmonic frequency observed far away from the heater frequency. Blagoveshchenskaya et al () analyzed in detail the narrowband SEE spectral features in the course of the X‐mode experiment on February 25, 2013, at a pump frequency of 5.423 MHz at Saint Peterburg, which is 1,200 km away from Tromsø.…”
Section: Introductionmentioning
confidence: 99%
“…Blagoveshchenskaya et al () analyzed in detail the narrowband SEE spectral features in the course of the X‐mode experiment on February 25, 2013, at a pump frequency of 5.423 MHz at Saint Peterburg, which is 1,200 km away from Tromsø. However, Blagoveshchenskaya et al (), , did not observe any spectral features within 200 kHz near Tromsø that were associated with X‐mode heating near the fourth gyroharmonic frequency.…”
Section: Introductionmentioning
confidence: 99%